PERILAKU SHARENTING ORANGTUA DI MAKASSAR - Astrid, Andi Fauziah (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2021)
Sharing behavior is the behavior of parents who like to share children's activities on social media. there are social media owned by parents as well as those made especially for the child. How is the digital behavior of parents in Makassar in spreading content about children?